The effects of time-variable absorption due to gamma-ray bursts in active galactic nucleus accretion discs. Issue 3 (20th March 2023) - Ray, Michael; Lazzati, Davide; Perna, Rosalba
ABSTRACT: Both long and short gamma-ray bursts (GRBs) are expected to occur in the dense environments of active galactic nucleus (AGN) accretion discs. As these bursts propagate through the discs they live in, they photoionize the medium causing time-dependent opacity that results in transients with unique spectral evolution. In this paper, we use a line-of-sight radiation transfer code coupling metal and dust evolution to simulate the time-dependent absorption that occurs in the case of both long and short GRBs. Through these simulations, we investigate the parameter space in which dense environments leave a potentially observable imprint on the bursts. Our numerical investigation reveals that time-dependent spectral evolution is expected for central supermassive black hole masses between 10 5 and 5 × 10 7 solar masses in the case of long GRBs, and between 10 4 and 10 7 solar masses in the case of short GRBs. Our findings can lead to the identification of bursts exploding in AGN disc environments through their unique spectral evolution coupled with a central location. In addition, the study of the time-dependent evolution would allow for studying the disc structure, once the identification with an AGN has been established. Finally, our findings lead to insight into whether GRBs contribute to the AGN emission, and which kind, thus helping to answer the question of whether GRBs can be the cause of some of the as-of-yet unexplained AGN time variability.